Designing in-vehicle voice assistants: Creating safer, integrated driver experiences - NGUYEN, CONNIE (KHANH); FALKENGREN, WILLIAM (My University, 2019)
Voice assistants are increasing in popularity with the rise of devices like smart speakers and screens. As people grow accustomed to using these assistants, it is likely they would want use the same voice assistant in their car. Many modern cars already support integration of voice assistants from both Apple and Google. In this project, voice assistants integrated into the vehicle and their effects on safety in terms of increased diverted attention and cognitive load are examined. Current voice assistants are also reviewed. Apple Siri and Google Assistants, two commercial voice assistants, are evaluated under the conditions of manual driver, as well as with longitudinal and lateral assistive drive features. New, improved design solutions and guidelines were evaluated through two prototypes with different approaches to solving found problems in existing voice assistants. The results indicate several similarities and differences in the existing design guidelines for the different voice assistants. Users provide input and thoughts about the existing solutions. New design solutions for decreasing distraction and cognitive load are presented. These new solutions can help continued research and further improvement of voice assistants within cars in the future to come.
Keywords: Voice Assistant; Voice Interaction; Driving; Safety; Attention; Cognitive Load; Design Guidelines